2017
DOI: 10.3390/en10111685
|View full text |Cite
|
Sign up to set email alerts
|

Using IEC 61850 GOOSE Service for Adaptive ANSI 67/67N Protection in Ring Main Systems with Distributed Energy Resources

Abstract: Smart Grids are electricity networks that use digital technology to co-ordinate the needs and capabilities of all generators, grid operators, end users and electricity market stakeholders in such a way that it can optimize asset utilization and operation while maintaining system reliability, resilience and stability. However, Smart Grids are increasingly proposing a much more distributed architecture with the integration of multiple Distributed Energy Resources (DERs) that demand different control and protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Available communication capacity for two SMV publishers in a high-availability seamless redundancy (HSR) network [13] is:…”
Section: The Timing Analysis Of Sampled Values Streamsmentioning
confidence: 99%
See 2 more Smart Citations
“…Available communication capacity for two SMV publishers in a high-availability seamless redundancy (HSR) network [13] is:…”
Section: The Timing Analysis Of Sampled Values Streamsmentioning
confidence: 99%
“…The experiment focused on the hard in the loop test with traditional current and voltage-operated protection relays and with sampled measured values according to IEC 61850-9-2LE. The comparison found that the relay protection function performance is very similar to that of classical substations, with the advantage of the data transmission in digital form.Reference [13] focused on the configuration of IEC 61850 GOOSE service for easy implementation with electric protection systems; the authors proposed an algorithm to achieve full implementation of the IEC 61850 instead of the hard wired network connection.Reference [14] focused on the reliability analysis of the cyber-physical interface matrix (CPIM) methodology. The test calculated the impact of the physical device failure and the communication devices failures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In [18] and [19], data gathered by several IEDs were used to improve the network fault location with the presence of DGs. In other cases, IEDs were provided with directional protection functionality where the adaptive protection settings were established by a control centre which communicated to the IEDs their setting parameters [20].…”
Section: Introductionmentioning
confidence: 99%
“…The first version focused only on communication networks and systems in substations. However, the second edition was expanded to cover communication networks and systems for power utility [1]. The standard mandates integration of all protection, control, measurement, and monitoring functions of a power system network at both the process and station levels.…”
Section: Introductionmentioning
confidence: 99%